Entrevista com o Prof. Manoel Correa de Andrade - Victor Antonio Peluso Júnior; Armen Mamigonian; Roland Luiz Pizzolatti; Maria Dolores Buss; Ewerton Vieira Machado (Geosul)
Entrevista com o Prof. Manoel Correa de Andrade